2015
DOI: 10.1007/978-3-319-24553-9_56
|View full text |Cite
|
Sign up to set email alerts
|

A Registration Approach to Endoscopic Laser Speckle Contrast Imaging for Intrauterine Visualisation of Placental Vessels

Abstract: Abstract. Intrauterine interventions such as twin-to-twin transfusion syndrome procedure require accurate mapping of the fetal placental vasculature to ensure complete photocoagulation of vascular anastomoses. However, surgeons are currently limited to fetoscopy and external ultrasound imaging, which are unable to accurately identify all vessels especially those that are narrow and at the periphery. Laser speckle contrast imaging (LSCI) is an optical method for imaging blood flow that is emerging as an intraop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Additionally, the design of the laparoscope as a hand-held tool makes it more vulnerable to user movement and vibrations. Image registration has been proven to be capable of compensating for considerable motion, and in future studies this technique should be applied to our processing algorithm [5,33,34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the design of the laparoscope as a hand-held tool makes it more vulnerable to user movement and vibrations. Image registration has been proven to be capable of compensating for considerable motion, and in future studies this technique should be applied to our processing algorithm [5,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic implementation of LSCI faces difficulties due to several technical issues including laser light source integration, fiber light guide coupling, and specular reflections from the tissue surfaces. Numerous rigid endoscopic LSCI systems have been explored by several research groups [5][6][7][8]. However, their systems are designed for different application areas and thus have limitations that make them unsuitable for minimally invasive surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned previously, we focus on LSCI and several studies have addressed the integration of the LSCI technique into an endoscope and demonstrated perfusion imaging, e.g., in the knee, 9 uterus, 10 gastrointestinal tract, 11 , 12 and deep brain. 13 While these studies highlighted the potential of LSCI for intra-surgery imaging, they relied on combining research grade (or standard vision) cameras with rigid endoscopes 9 , 10 , 11 , 12 or, in limited way, fiber image guides. 14 Direct-view into brain using miniature optics was used for deep brain imaging, but with highly disruptive endoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, mapping vasculature and perfusion of placenta allows for a powerful test during twin-to-twin transfusion syndrome procedure. 10 Capture and analysis of speckle patterns is also an established imaging method in ultrasound context 32 and we re-deploy it optically. Hence, this setup exploits the imaging function of (commercial) LSCI imagers while reducing the size of the required hardware components to enable assessment of internal organs or tissues or orifices within the body.…”
Section: Introductionmentioning
confidence: 99%